Delayed Primary and Specialty Care: The Coronavirus Disease–2019 Pandemic Second Wave. (7th June 2020) - Weinstein, Eric; Ragazzoni, Luca; Burkle, Frederick; Allen, Mea; Hogan, David; Della Corte, Francesco
ABSTRACT: Time is of the essence to continue the pandemic disaster cycle with a comprehensive post-COVID-19 health care delivery system RECOVERY analysis, plan and operation at the local, regional and state level.The second wave of COVID-19 pandemic response are not the ripples of acute COVID-19 patient clusters that will persist until a vaccine strategy is designed and implemented to effect herd immunity. The COVID-19 second wave are the patients that have had their primary and specialty care delayed. This exponential wave of patients requires prompt health care delivery system planning and response.